Pemberdayaan Lintas Sektoral dalam upaya Mewujudkan Masyarakat Peduli Kesehatan dan Keselamatan Berkendara - Nina Dwi Lestari; Arif Wahyu Setyo Budi; Al Afik (Universitas Mathla'ul Anwar Banten, 2019)
CROSS SECTORAL EMPOWERMENT IN AN EFFORT TO REALIZE A COMMUNITY THAT CARES ABOUT HEALTH AND SAFETY DRIVING. Traffic accidents are a global phenomenon with increasing events that can result in losses and deaths. The most dominant human factor is related to traffic accident between vehicle and physical environment. WHO reports that around 1.2 million people die each year from road accidents and are a leading cause of death among young people aged 15-29 years. Partners in this program are residents of Rt 24, RW 12, Tegowanu, Kaliagung, Sentolo, Kulon Progo. The problems faced by partners are the high driving accidents in the partner area, due to geographical conditions of the road, vehicles that pass at high speeds from both directions, and poor driving behavior. The methods used in this program are community education, demonstrations, case simulations and family counseling. The result of this program are that there is an increase in partner’s knowledge related to driving health and safety, as much as 80% of participants are able to re-evacuate the techniques of evacuation, transportation and first aid in an accident at the location. It requires the efforts of the relevant parties to continue to accustom the culture of healthy and safety driving.